Case report: A case of injury to the infrapatellar branch of the saphenous nerve caused by medial approach in knee arthroscopy - Tan, Jiyang; Wang, Xunhao; Xiong, Fei; Qian, Jun; Ying, Qiuwen; Mi, Jingyi (Frontiers in Neurology, 2023)
We present the case of a 72-year-old man who was referred to our department for treatment of pain on the anteromedial infrapatellar side of the right knee with sensory disturbance that began 2 years earlier. The patient previously underwent right knee arthroscopy at another hospital for a meniscus injury 2 years earlier, which relieved his knee pain, but pain and discomfort near the incision of the medial portal persisted. Given this situation, various physical treatments, such as ice compress, were administered postoperatively. However, the symptom was only partially relieved before discharge. Subsequently, the patient visited two other hospitals and began taking oral pregabalin and duloxetine for treatment of the pain based on a diagnosis of right common peroneal nerve injury. The pain in the same dermatomal distribution was slightly relieved, but a withdrawal reaction was observed. However, the results of an ultrasound at our hospital indicated that the right medial quadriceps femoris tendon showed a hypoechoic area suggesting inflammatory changes. Physical examination of the right knee detected atrophy of the quadriceps femoris muscle, decreased muscle strength (M4), obvious tenderness in the medial side, radiating pain along the anterior tibia, and sensory disturbance (S3+); the results of a drawer test, McMurray test, pivot shift test, and lateral stress test were negative. Based on the aforementioned evidence, a diagnosis was made of injury to the infrapatellar branch of the saphenous nerve, after which neurolysis of the nerve in question was carried out. An enlarged incision was made along the original medial approach. Scar hyperplasia was observed after careful separation of the subcutaneous tissue. During neurolysis, branches were found wrapped in the scar; their continuity and integrity were confirmed after relief. The released nerve was placed in a physiological position. The patient's pain was clearly relieved, and numbness disappeared on the first postoperative day. At 1-month follow-up, all symptoms were found to have resolved.